(untitled) (Eduscotech, 2023)
The Teaching Games for Understanding (TGfU) learning model serves as an innovative approach that emphasizes students’ comprehension of game tactics and strategies while encouraging critical thinking and problem-solving skills. At the same time, the urgency of strengthening character education during the golden age of primary school students, especially amid the challenges of the Digital 5.0 era, requires holistic and participatory teaching methods. This community service program aims to integrate the potential of TGfU and creative activities as a strategic solution for instilling character values in students living in metropolitan coastal areas with limited access to self-development facilities. The program was implemented using a blended method with a Project-Based Learning (PjBL) approach targeting teachers at SDN Gambiran, Maospati District. The activities began with an interactive lecture to explore teachers’ prior experiences and stimulate critical thinking, followed by a workshop involving the development of mini-media projects related to TGfU and character education. The program concluded with a post-test evaluation and a structured feedback session. The outcomes include both physical and non-physical products. The physical outputs consist of a creative activity guide module, collections of student creations, and prototypes of educational teaching aids. The non-physical outputs involve improved student knowledge of character values, enhanced social skills such as collaboration and teamwork, and strengthened teacher competence in implementing innovative character-based learning. In addition, this program contributes academic outputs in the form of a scientific publication in a reputable Community Service (PkM) journal and mass media dissemination. Overall, the program reinforces students’ character formation and supports schools’ roles as agents of social change.